Strategi Kolaboratif Kepala Madrasah dan Guru dalam Membangun Budaya Mutu Pendidikan Islam melalui Sistem Penjaminan Mutu Pendidikan di MTsN 1 Sidoarjo - Adinda Rusdiana; Zakiyah Darojah; Sahudi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to analyze the collaborative strategies of principals and teachers in building a quality culture of Islamic education through the Education Quality Assurance System (SPMP) at MTsN 1 Sidoarjo. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The informants consisted of the principal, teachers, and educational staff. Data were analyzed through data reduction, data display, and conclusion drawing, supported by triangulation. The findings indicate that a quality culture is developed through participatory planning, academic supervision, periodic evaluation, and teacher competency development. Supporting factors include strong teamwork, effective communication, and participatory leadership, while administrative burdens and limited time become the main obstacles. Effective collaboration between principals and teachers plays an important role in sustaining the quality culture of Islamic education.